Investigating the effect of using a home safety training application by caregivers on accident risk management in the elderly - Mahdie Dehnavi; Najmeh Valizadeh zare; Seyd Reza Mazlom; Samira Mohajer; Tahereh Sadeghi; Mohammad Namazinia; Danial Baghie (Experimental Gerontology)
Background: The increasing elderly population is a complex and globally significant phenomenon impacting various sectors of society, including healthcare. By 2050, it is projected that one-fourth of Iran's population will be elderly. Falls are a major concern among the elderly, leading to physical and psychological injuries and imposing significant financial burdens on healthcare and social systems. Given the widespread acceptance of smartphones and mobile health applications, however limited research has been conducted on the effectiveness of mobile applications in training caregivers for home safety and accident prevention in elderly populations. Methods: This randomized clinical trial was conducted in 2022 in Mashhad, Iran. The sample consisted of 66 elderly caregivers, randomly assigned to intervention and control groups. Data collection tools included a demographic information questionnaire and the Home Safety Self-Assessment Tool (HSSAT). The intervention group used a home safety educational application, while the control group received educational brochures. Data were analyzed using SPSS software and appropriate statistical tests. Results: Sixty-two elderly caregivers participated in the study, with a mean age of 72 ± 37.7 years. The chi-square test showed no significant difference in gender distribution between the intervention and control groups (p = 0.060). The majority of participants in both groups had a high school education. Before the training, there was no significant difference in the mean accident risk management scores between the two groups (p = 0.713). Repeated measures ANOVA revealed a significant time effect (F(1, 60) = 408, p < 0.001, Partial η2 = 0.872) and a significant group effect (F(1, 60) = 5, p = 0.025, Partial η2 = 0.081). Additionally, the interaction between time and group was significant (F(1, 60) = 6, p = 0.015, Partial η2 = 0.095), indicating a greater improvement in accident risk management scores in the intervention group compared to the control group. Conclusions: The use of home safety educational applications can effectively reduce the risk of accidents and improve preventive measures management among the elderly. These modern educational tools can alleviate the burden on healthcare systems and save costs associated with in-person training. Future research should continue exploring innovative educational methods to enhance the safety and well-being of the elderly population. Trial registration: This study was registered in the Iranian Registry of Clinical Trials (no. IRCT20210610051532N1) on 07/09/2021.